PENERAPAN PENDEKATAN SCIENTIFIC PADA MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE UNTUK MENINGKATKAN PEMAHAMAN SISWA DI KELAS VII SMPN 6 PALU - H. M. Tawil, Akhyar; Ismaimuza, Dasa; Rochaminah, Sutji (Jurnal Elektronik Pendidikan Matematika Tadulako, 2014)
The aim of this research was to obtain the description of application scientific approach at cooperative learning of think pair share (TPS) to improve student understanding on line and angel in class VII Unggulan I SMP Negeri 6 Palu. The design of this research to Kemmisâ and Mc. Taggartsâdesign those are: (1) planning, (2) action, (3) observation and (4) reflection. This research was conducted in two cycles. The research result indicating that the application of scientific approach at cooperative learning of think pair share (TPS) can increase students understanding on line and angel through activities: (1) step think, students tried to copy and measured to find the angels which have same size, observed the picture of two parallel lines are intersected by another line, (2) step pair, students with they pair associating the relationship of the angels that are formed from two parallel lines are intersected by another line,(3) step share, studentstogether with they group communicated their discovery result in fron of the class